2017
DOI: 10.1080/2162402x.2017.1393596
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of tumor-associated macrophages switches the epigenetic profile of pancreatic cancer infiltrating T cells and restores their anti-tumor phenotype

Abstract: Pancreatic Ductal Adenocarcinoma (PDA) is characterized by a complex tumor microenvironment that supports its progression, aggressiveness and resistance to therapies. The delicate interplay between cancer and immune cells creates the conditions for PDA development, particularly due to the functional suppression of T cell anti-tumor effector activity. However, some of the mechanisms involved in this process are still poorly understood. In this study, we analyze whether the functional and epigenetic profile of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 66 publications
(74 reference statements)
5
51
0
Order By: Relevance
“…Macrophages have been considered as key components for the survival of many tumors [ 31 , 37 , 38 , 39 ]. These tumor-associated macrophages (hTAMs) are educated by cancer cells and the stromal microenvironment to block the action of the adaptive immune system to fight and prevent tumor growth [ 38 , 40 , 41 , 42 , 43 ]. Not only do hTAMs contribute to avoiding immunosuppression, but they also participate in other tumor-supporting functions, such as neovascularization and the spread of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages have been considered as key components for the survival of many tumors [ 31 , 37 , 38 , 39 ]. These tumor-associated macrophages (hTAMs) are educated by cancer cells and the stromal microenvironment to block the action of the adaptive immune system to fight and prevent tumor growth [ 38 , 40 , 41 , 42 , 43 ]. Not only do hTAMs contribute to avoiding immunosuppression, but they also participate in other tumor-supporting functions, such as neovascularization and the spread of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…One additional observation was the decrease in the cell surface levels of PD-L1, which might contribute to reinforce the immune surveillance action of the adaptive immune system against tumor cells [ 43 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A preclinical study recently showed in a chronic lymphocytic leukemia mouse model that trabectedin induced leukemic cell death and depletion of the immuno-suppressive myeloid-derived suppressor cells and TAMs [102]. Anti-tumor activity by trabectedin, through effects on TAMs, has also been reported in pre-clinical models of skeletal metastatic prostate tumor, melanoma, and pancreatic tumor [103][104][105].…”
Section: Strategies To Deplete Tamsmentioning
confidence: 97%
“…by activating the expression of NK cellactivatory ligands). 15,141,[334][335][336][337][338][339] Finally, most immunooncology trials do not select chemotherapeutics based on their immunostimulatory potential (which in many cases does not manifest at clinically employed dose regimens), but rather based on their use a standard-of-care for selected indications. At least in some cases, such a design precludes the activation of clinically meaningful anticancer immune responses and hence limits the clinical benefit of combinatorial regimens.…”
Section: Introductionmentioning
confidence: 99%